Development and Validation of Multimedia-Based Interactive Learning Media to Enhance Students’ Conceptual Understanding of the Periodic Table in Chemistry Education - Wahyu Arfian Saputra (Journal of Chemical Learning Innovation, 2026)
Purpose of the study: This study aims to develop and validate multimedia-based interactive learning media to enhance students’ conceptual understanding of the periodic table in chemistry education. Methodology: The research employed a Research and Development (R&D) approach using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The developed media integrates text, images, animations, and interactive features to facilitate meaningful learning experiences. Main Findings: The results of expert validation indicate that the media is highly valid, with an average score of 87.5% from media experts and 90.0% from subject matter experts. The implementation results show positive student responses, with an average score of 88.25%, indicating high levels of engagement and usability. Furthermore, the effectiveness test reveals a significant improvement in students’ conceptual understanding, as indicated by an increase in post-test scores and a moderate N-gain of 0.58. Novelty/Originality of this study: Novelty of this study lies in the integration of interactive multimedia features with a systematic validation process, specifically designed to address conceptual challenges in learning the periodic table. This study provides an innovative and empirically validated learning solution that contributes to improving the quality of chemistry education.